Poetry - Chang-dong, Lee; Kim Hyunseok; Yoon Jeong-hee; Lee Davit; Kim Hira (Arrow Films, 2011)
For Mija, a 66-year-old who has just enrolled in her first poetry-writing workshop at the local community center, nature is where one looks for poetic inspiration. But there’s a darker kind of beauty running through the film by writer-director Lee Chang-dong. The film’s most moving scenes, in a film with many moving scenes, are shot like reality-TV confessionals. They’re personal stories told by Mija and her fellow students, who face the camera head-on while reminiscing about love, loss and longing. [www.washingtonpost.com]